Action research restoration trials, Baringo County, Kenya - Ng'ang'a, Irene N.; Flintan, Fiona E.; Sircely, Jason A. (International Livestock Research Institute, 2023)
A report of restoration trials being conducted by ILRI to assess the viability and impacts of short-resting and use of exclosures in pastoral communities implementing partictipatory rangeland management (PRM) in Baringo County, Kenya